By His Excellency John Hancock, Esq ; governor of the commonwealth of Massachusetts, A proclamation for a day of thanksgiving : ... Thursday the eleventh day of December next (the day recommended by the Congress to all the states) ... Given at the council-chamber in Boston, the eighth day of November ... one thousand seven hundred and eighty three . ([publisher not identified], 1783)
November 10, 1783 Proclamation by Governor John Hancock setting December 11th as a day of thanksgiving for the cessation of war against Britain, the sovereignty of the United States, and other blessings. Of note, the Treaty of Paris was signed on September 3, 1783, bringing an end to the Revolutionary War.